2023
DOI: 10.3390/cimb45030148
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin Receptor Substrate 2 Mediates the Action of Insulin on HeLa Cell Migration via the PI3K/Akt Signaling Pathway

Abstract: Insulin signaling plays an important role in the development and progression of cancer since it is involved in proliferation and migration processes. It has been shown that the A isoform of the insulin receptor (IR-A) is often overexpressed, and its stimulation induces changes in the expression of the insulin receptor substrates (IRS-1 and IRS-2), which are expressed differently in the different types of cancer. We study the participation of the insulin substrates IRS-1 and IRS-2 in the insulin signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have identified a minimum of seven insulin-like IGFBPs that have the capability to bind to insulin-like growth factor I (IGF-I) and IGF-II, thereby regulating their activity and signaling functionality ( Izutsu et al, 2022 ; Alterki et al, 2021 ; Hjortebjerg et al, 2021 ; Agerholm et al, 2020 ). IGFBPs and IGF play pivotal roles in the IGF signaling pathway, exerting significant impacts on tumor initiation, progression, metastasis, and chemoresistance ( Han & Kim, 2021 ; Lee, Tocheny & Shaw, 2022 ; Lee et al, 2022 ; Du et al, 2017 ; Martinez Baez et al, 2023 ) that lead to antitumor effects ( Cai, Dozmorov & Oh, 2020 ). For example, Kuhn et al (2023) discovered that IGFBP3 inhibited lung cancer cell invasion and proliferation and was linked to the patients’ enhanced survival.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a minimum of seven insulin-like IGFBPs that have the capability to bind to insulin-like growth factor I (IGF-I) and IGF-II, thereby regulating their activity and signaling functionality ( Izutsu et al, 2022 ; Alterki et al, 2021 ; Hjortebjerg et al, 2021 ; Agerholm et al, 2020 ). IGFBPs and IGF play pivotal roles in the IGF signaling pathway, exerting significant impacts on tumor initiation, progression, metastasis, and chemoresistance ( Han & Kim, 2021 ; Lee, Tocheny & Shaw, 2022 ; Lee et al, 2022 ; Du et al, 2017 ; Martinez Baez et al, 2023 ) that lead to antitumor effects ( Cai, Dozmorov & Oh, 2020 ). For example, Kuhn et al (2023) discovered that IGFBP3 inhibited lung cancer cell invasion and proliferation and was linked to the patients’ enhanced survival.…”
Section: Discussionmentioning
confidence: 99%
“…1a) (Supplementary information 1). Alterations in epidermal growth factor receptor (EGFR) [36,37], fibroblast growth factor receptor (FGFR) [38,39], platelet-derived growth factor receptor (PDGFR) [40,41], vascular endothelial growth factor receptor (VEGFR) [42,43], hepatocyte growth factor (HGF) [44,45], leukocyte receptor tyrosine kinase (LTK) [46,47], and insulin receptor (INSR) [48,49] family genes make a significant contribution to treatment failure mainly through the activation of PAM pathway (Fig. 1b) (Supplementary information 1).…”
Section: Pam Signaling In Cancer Rtk Overactivation In Cancermentioning
confidence: 99%
“…IRS-1 interacts with the catalytic p110 subunit, leading to increased PIP3 and p85 regulatory subunit sequestration, which is associated with increased insulin resistance and can explain the side effects of PIK3CA inhibitors, such as hyperglycemia. IRS-1 stimulation increases GLUT-1 receptor expression and downregulates GLUT4 membrane translocation [248][249][250][251].…”
Section: Insulin Derived Pi3k Activationmentioning
confidence: 99%